Evolution of European Sanctions: From Individual Measures to Consolidated Policy - V. A. Silaeva (Международная аналитика)
In modern world, as more and more states are reluctant to apply direct military force, the role of non-military instruments of coercion such as economic sanctions augments in international relations. In recent years economic sanctions have become firmly anchored in the system of European instruments of foreign policy. Although their implementation and monitoring still requires substantial improvements, progress and high level of consolidation can be witnessed on several recent examples. The article focuses on the evolution of the institutional basis and the mechanisms of coordination of the European Union policy in the sphere of restrictive measures, as well as detailed analysis of current tools of elaboration and implementation of various economic foreign instruments. Three stages can be distinguished in the evolution of European restrictive measures. Originally, there was no coordination as sanctions were introduced by nation states separately and individually. However, with the rise of economic interdependency of the allies there appeared new instruments for the exchange of information and opinions that have evolved into strictly binding mechanisms we can witness today. The example of Iranian sanctions shows what new schemes have been elaborated to increase the effectiveness of sanctions policy and how they have spread and developed, including to work out sanctions against Russia.